Research Progress in Supersonic Two-phase Separation by Expansion and Refrigeration Liquefaction - Chen Baosheng; Zeng Yupei; Zou Aihong; Luo Ercang (Zhileng xuebao, 2024)
Supersonic expansion cooling combined with swirl separation technology is a novel method for gas liquefaction separation that has been mainly employed to separate high freezing point components from multi-component gases in recent years. In this study, two typical structures of supersonic swirl separators are introduced. Thereafter, the theoretical development, numerical simulation, experimental research, and molecular simulation of the condensation phase transformation in the Laval nozzle are summarized. Subsequently, the shockwave problem and structural optimization are analyzed and recapitulated. Numerous experiments and field applications demonstrate the advantages of the device; for example, it saves energy and is environmentally friendly, it has no moving parts, and it eliminates the need to add chemical agents. It has thus been widely used in the field of natural gas purification treatment. Future research can focus on the condensation phase transformation mechanism of single-component and multi-component gases and on improving liquefaction efficiency to promote the application of supersonic swirl separation technology in liquefaction and refrigeration processes, particularly in the refrigeration temperature range and cryogenic temperature range of hydrogen and helium.